APLIKASI PEMBELAJARAN UNGGAH-UNGGUH BAHASA JAWA DIALEK YOGYAKARTA BERBASIS ANDROID - Palupi, Nita Siwi; Fitriastuti, Fatsyahrina; Putra, Jeffry Andhika (Universitas Janabadra, 2019)
Javanese is the mother tongue of the Javanese people. Javanese language is not only as a medium of communication but has a noble philosophical value. At this time, some Javanese people, especially young people, do not understand Javanese. They are not able to speak Javanese properly according to Javanese language. Low understanding of Javanese means that Javanese people prefer to use Indonesian rather than Javanese. Javanese language has a value of life, such as manners, politeness, and sincerity. Given the importance of the function of Javanese for the community, the existence of Javanese needs to be preserved. The application design process aims to facilitate the Javanese community, especially young people in learning Javanese so that more Javanese people master Javanese. Some tools used in building applications include Android Studio, Adobe Flash CS 6, and CorelDraw X4. The results of trials that have been done, the application can run well on version 4.2 (Jellybean) and above. The application presents a pretty attractive appearance, easy to use with language that is easy to understand.Â Kata Kunci: Javanese, Android, Unggah-ungguh, Yogyakarta